The relationship between the dietary protein intake and functional ovarian cysts - Fazeli, Elham; Tafazoli, Mahin; Nematy, Mohsen; Bahri, Narjes (Progress in Nutrition, 2016)
Summary. Objective: Although ovarian cysts are of an unknown etiology, there is some information about the associated risk factors. To considering the high prevalence of ovarian cysts and the associated complications. This study aimed to assess the relationship between the dietary protein intake and the functional ovarian cysts in women at reproductive age. Methods: This case-control study was conducted on 264 women, aged 15-49 years. The case group consisted of women with the functional ovarian cysts (n=132) and the control group included the healthy individuals (n=132). The Pregnant women, females with a prior history of infertility, and the menopausal women were excluded in the study. A demographic questionnaire was used for collecting the patients’ demographic information, medical and midwifery history. The dietary protein intake was measured using a Food Frequency Questionnaire. For the data analysis, t-test, χ2, and regression analysis were performed, using SPSS version 16. Results: The mean levels of protein intake were 104.62±93.63 and 86.20±41.52 g in the case and control groups, respectively. A significant relationship was observed between the dietary protein intake and the functional ovarian cysts (P=0.04). Conclusion: To considering the direct relationship between high protein consumption and the functional ovarian cysts, appropriate educational programs are needed.